(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In her path-breaking essay Towards Black FeministCriticism, Barbara Smith asserts “It is galling that ostensible feminists …have been so blinded to the implications of any womanhood that is not whitewomanhood and that they have yet to struggle with the deep racism in themselvesthat is at the source of this blindness.” (Eagleton 123) This dissentiousstatement comes after Feminist Criticism has dominated our intellectualprojects and processes since the 1970s. Current academic trends make it evidentthat Black American Literature, of the women in particular and morespecifically Black feminist Criticism is a hesitantly advancing sub-culturethat hardly has been anthologized or acquired critical readership that is notbiased or marginalized. Women’s literature and literary criticism, denotingwhite-women’s literature or those conforming to the norms of Feminism advocatedby the white feminists, have become increasingly academically fashionable thelikes of Audre Lorde, Sojourner Truth, Harriet Tubman, Wells Barnett, Gloria T.Hull or bell hooks whose works have a common essential sensitivity to the theircomplex life-situation originating out of their combined racial and sexualidentity that contextualizes oppression and struggles against oppression. AsSmith explains further “The role that criticism plays in making a body ofliterature recognizable and real hardly needs to be explained here. Thenecessity for non-hostile and perceptive analysis of works written by personsoutside the "mainstream" of white/male cultural rule has been provenby the Black cultural resurgence of the 1960s and 1970s and by the even morerecent growth of feminist literary scholarship. For books to be real andremembered they have to be talked about. For books to be understood they mustbe examined in such a way that the basic intentions of the writers are at leastconsidered.” (Eagleton 123)